PERANCANGAN RUANG PUBLIK KREATIF DI DUTA MAS FATMAWATI - Verrel Moalim; Samsu Hendra Siwi (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
In the 2000s the Duta Mas Fatmawati area was a "live" area and crowded with visitors, but now it looks deserted. Many shophouses are abandoned and abandoned by their residents. Several things that affect this condition, one of which is the construction of MRT stations and tracks in 2013. This development makes access difficult because many roads have to be closed during the construction process, causing congestion and difficulty in getting parking. this causes the interest of visitors to be lost. Even after the completion of the MRT construction, the Duta Mas Fatmawati area has not shown a significant increase. Many things affect it, such as arid areas and lack of greenery, roads with potholes due to former construction and frequent traffic jams and floods at certain points. A small-scale intervention using the urban acupuncture method is needed that is able to solve environmental problems while also being a water catchment area in the form of a creative public space that utilizes the MRT and the many bus stop points in the Duta Mas Fatmawati area. The existence of this creative public space, of course, in addition to solving existing problems in the Duta Mas Fatmawati area, is also an attraction that can attract tourists from other areas and of course can accommodate and improve the economy of the surrounding community. Keywords:  Urban Acupuncture; Creative Public Space; Retail Abstrak Pada tahun 2000-an kawasan Duta Mas Fatmawati merupakan kawasan yang “hidup”dan ramai pengunjung, namun sekarang kondisinya terlihat sepi. Banyak ruko-ruko yang terbengkalai dan ditinggalkan oleh penghuninya. Beberapa hal yang mempengaruhi kondisi ini salah satunya adalah dibangunnya stasiun dan lintasan MRT pada tahun 2013. Pembangunan ini menyebabkan akses menjadi sulit karena banyak jalan yang harus ditutup selama proses pembangunan sehingga menimbulkan kemacetan dan sulit mendapatkan parkir. Hal ini menyebabkan minat pengunjung menjadi hilang. Setelah selesainya pembangunan MRT pun kawasan Duta Mas Fatmawati masih belum menunjukkan peningkatan yang signifikan. Banyak hal mempengaruhinya seperti daerah yang gersang dan kurang penghijauan,  jalan yang berlubang akibat bekas pembangunan dan sering terjadi kemacetan serta banjir pada titik-titik tertentu. Diperlukan sebuah intervensi skala kecil menggunakan metode akupunktur perkotaan yang mampu menyelesaikan masalah lingkungan selain itu juga menjadi daerah resapan air yang berupa ruang publik kreatif yang memanfaatkan MRT dan banyaknya titik pemberhentian bus pada daerah Duta Mas Fatmawati. Keberadaan ruang publik kreatif ini tentunya selain menyelesaikan masalah yang ada pada kawasan Duta Mas Fatmawati juga menjadi atraktor yang dapat menarik wisatawan dari daerah lain dan tentunya  dapat mewadahi dan meningkatkan perekonomian masyarakat sekitar.